2020
DOI: 10.1111/vde.12873
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum Interleukin 34 (IL‐34) and correlation with severity and pruritus scores in client‐owned dogs with atopic dermatitis

Abstract: Background Atopic dermatitis (AD) is a common inflammatory skin disease of dogs. Interleukin (IL)‐34 is a monocyte/macrophage growth factor, produced mainly by keratinocytes, that has been implicated in several human inflammatory conditions including human AD. Hypothesis Canine serum IL‐34 concentrations are increased in dogs with AD and correlate with clinical lesion and pruritus scores. Animals Forty seven client‐owned dogs diagnosed with AD and 25 healthy, unaffected control dogs. Methods and materials A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…A recent study in atopic dogs reported an increased expression of IL‐34 in the serum as compared with healthy controls and furthermore that this correlated with disease severity 63 . However, concentrations did not decrease after glucocorticoid or oclacitinib therapy.…”
Section: The Aberrant Immune Responsesmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study in atopic dogs reported an increased expression of IL‐34 in the serum as compared with healthy controls and furthermore that this correlated with disease severity 63 . However, concentrations did not decrease after glucocorticoid or oclacitinib therapy.…”
Section: The Aberrant Immune Responsesmentioning
confidence: 89%
“…62 A recent study in atopic dogs reported an increased expression of IL-34 in the serum as compared with healthy controls and furthermore that this correlated with disease severity. 63 However, concentrations did not decrease after glucocorticoid or oclacitinib therapy. The authors postulated that this may be linked to IL-34 being produced by damaged keratinocytes rather than immune cells.…”
Section: The Role Of the Microbial Composition Of Atopic Skinmentioning
confidence: 90%
“…Treatment response may be inversely related to the severity of skin lesions in CAD (9,14,24). Because the skin lesions in the lokivetmab group were more severe than those in the oclacitinib group at the start of the study, it may be difficult to compare the clinical efficacy of these drugs in improving skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, client-owned dogs with AD showed significantly higher serum IL-34 concentrations compared to healthy dogs with a significant positive correlation with CADESI-04 and pVAS scores. 108 These results may indicate a different role of IL-34 in canine compared to human AD. However, concentrations of IL-34 remained increased in atopic dogs during glucocorticoid or oclacitinib treatment despite the clinical improvement, 108 which may suggest that IL-34 is not of major importance in the pathogenesis of cAD.…”
Section: Interleukin-34mentioning
confidence: 95%